Green Product Differentiation as a Strategy to Enhance the Competitive Advantage of Handicraft SMEs - Mulyani Mulyani; Siti Titta Partini (Acman: Accounting and Management Journal, 2026)
Waste-based handicraft SMEs face increasing challenges in sustaining competitive advantage despite the growing demand for environmentally friendly products. This study aims to formulate a sustainable product differentiation strategy for KJL Art & Craft through an analysis of its internal and external business environment using the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and Internal–External (IE) matrix. A descriptive case study approach was employed, with data collected through semi-structured interviews, observation, documentation, digital media review, and literature analysis. The results show an IFE score of 3.41 and an EFE score of 2.71, positioning the business in Cell IV (Grow and Build) of the IE matrix. These findings indicate strong internal capabilities and a moderate ability to respond to external opportunities and challenges. The recommended strategy focuses on sustainable product differentiation by leveraging recycled materials, distinctive product designs, and artisan craftsmanship, supported by green digital marketing, product innovation, market development, and internal capacity enhancement. This study contributes practical strategic recommendations for waste-based handicraft SMEs seeking to strengthen their sustainable competitive advantage in an increasingly competitive market.